ANALISIS KEPUASAN PELANGGAN PADA PT. PLN (PERSERO) ULP KARANGASEM MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) - WINADRI, NI KETUT ANDI; PASEK, I KETUT; MARHAENI, KADEK ENI (GANEC SWARA, 2024)
This research aims to analyse the level of customer satisfaction at PT. PLN (Persero) ULP Karangasem. This research was conducted on customers of PT. PLN (Persero) ULP Karangasem with a total sample of 125 respondents, where the sampling technique used was purposive sampling. The results of calculating the average importance obtained an average value of 4.37, while performance had an average value of 4.35, Based on the analysis of the gap between importance and performance, there were 20 indicators that had a negative value, which means the level of customer satisfaction was in the less satisfied category, so it needed to be improved. Based on the Importance Performance Analysis diagram, there are 8 indicators that are included in quadrant A, including if there is an error in recording the electricity account, it will be re-checked as soon as possible (R4), billing information according to usage (R5), officers respond well to customer questions (RS2), officers are ready to serve customers (RS4), information conveyed by officers is clear, correct, and consistent (A2), provide certainty of action after customers report complaints (A5), officers understand specific needs customers (E1), ensuring customers leave satisfied (E4).